Germ Cell Drivers: Transmission of Preconception Stress Across Generations - Duffy, Korrina A.; Bale, Tracy L.; Epperson, C. Neill (Frontiers in Human Neuroscience, 2021)
Exposure to stress can accelerate maturation and hasten reproduction. Although potentially adaptive, the trade-off is higher risk for morbidity and mortality. In humans, the intergenerational effects of stress have been demonstrated although the precise mechanisms are unknown. Strikingly, even if parental stress occurs prior to conception, as adults, their offspring show worse mental and physical health. Emerging evidence primarily from preclinical models suggests that epigenetic programming may encode preconception stress exposures in germ cells, potentially impacting the phenotype of the offspring. In this narrative review, we evaluate the strength of the evidence for this mechanism across animals and humans in both males and females. The strongest evidence comes from studies of male mice, in which paternal preconception stress is associated with a host of phenotypic changes in the offspring and stress-induced changes in the small noncoding RNA content in sperm have been implicated. Two recent studies in men provide evidence that some small noncoding RNAs in sperm are responsive to past and current stress, including some of the same ones identified in mice. Although preliminary evidence suggests that findings from mice may map onto men, the next steps will be (1) considering whether stress type, severity, duration, and developmental timing affect germ cell epigenetic markers, (2) determining whether germ cell epigenetic markers contribute to disease risk in the offspring of stress-exposed parents, and (3) overcoming methodological challenges in order to extend this research to females.